Conversion of calcium‐l‐methylfolate and (6S)‐5‐methyltetrahydrofolic acid glucosamine salt into dietary folate equivalents. (24th August 2022) - ,; Turck, Dominique; Bohn, Torsten; Castenmiller, Jacqueline; De Henauw, Stefaan; Hirsch‐Ernst, Karen Ildico; Knutsen, Helle Katrine; Maciuk, Alexandre; Mangelsdorf, Inge; McArdle, Harry J.; Naska, Androniki; Peláez, Carmen; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver a scientific opinion on the conversion of calcium‐l ‐methylfolate and ( 6S )‐5‐methyltetrahydrofolic acid glucosamine salt (collectively called 5‐MTHF hereafter) into dietary folate equivalents (DFE). Following a systematic review, the conclusions of the opinion are based on one intervention study in adults for intakes < 400 μg/day and three intervention studies in adults for intakes ≥ 400 μg/day. At intakes below 400 μg/day, folic acid (FA) is assumed to be linearly related to responses of biomarkers of intake and status and is an appropriate comparator for deriving a DFE conversion factor for 5‐MTHF. It is proposed to use the same factor as for folic acid for conversion of 5‐MTHF into DFE for intakes < 400 μg/day. As such intake levels are unlikely to be exceeded through fortified food consumption, the conversion factor of 1.7 relative to natural food folate (NF) could be applied to 5‐MTHF added to foods and to food supplements providing < 400 μg/day. At 400 μg/day, 5‐MTHF was found to be more bioavailable than folic acid and a conversion factor of 2 is proposed for this intake level and for higher intakes. The derived DFE equations are DFE = NF + 1.7 × FA + 1.7 × 5‐MTHF for fortified foods and food supplements providing intakes < 400 μg/day; and DFE = NF + 1.7 × FA + 2.0 × 5‐MTHF for food supplements providing intakes ≥ 400 μg/day. Although this assessment applies to calcium‐L‐methylfolate and 5‐MTHF glucosamine salt, it is considered that the influence of the cation on bioavailability is likely to be within the margin of error of the proposed DFE equations. Therefore, the proposed equations can also be applied to 5‐MTHF associated with other cations.